2021
DOI: 10.1111/jth.15516
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for gastrointestinal bleeding in patients with gastrointestinal cancer using edoxaban

Abstract: Background In the Hokusai VTE Cancer study, the risk of major bleeding was 2.9% higher in the edoxaban group compared with the dalteparin group, mainly due to more gastrointestinal bleedings in patients with gastrointestinal cancer. The identification of risk factors for gastrointestinal bleeding may help to guide the use of DOACs in these patients. Objectives To evaluate risk factors for gastrointestinal bleeding in patients with gastrointestinal cancer receiving edoxaban. Patients/Methods In this nested case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…[23][24][25][26][27][28][29][30] A nested case-control study in patients with GI cancer randomized to edoxaban in the Hokusai VTE Cancer study has reported that advanced cancer and low hemoglobin levels were associated with bleeding. 31 Our study confirms that some of these factors are also associated with bleeding in cancer patients taking full-dose apixaban. In a recently published sub-analysis of the Caravaggio study, ECOG status of 2, genitourinary cancer, upper GI cancer, and nonresected luminal GI cancer were the predictors of major bleeding.…”
Section: Discussionsupporting
confidence: 84%
“…[23][24][25][26][27][28][29][30] A nested case-control study in patients with GI cancer randomized to edoxaban in the Hokusai VTE Cancer study has reported that advanced cancer and low hemoglobin levels were associated with bleeding. 31 Our study confirms that some of these factors are also associated with bleeding in cancer patients taking full-dose apixaban. In a recently published sub-analysis of the Caravaggio study, ECOG status of 2, genitourinary cancer, upper GI cancer, and nonresected luminal GI cancer were the predictors of major bleeding.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, Bosch et al, in a nested case–control study in patients with gastrointestinal cancer randomized to edoxaban in the Hokusai VTE Cancer study, found that advanced cancer and low hemoglobin levels were associated with an increased risk of gastrointestinal bleeding in patients with gastrointestinal cancer receiving edoxaban. 22 In the SELECT-D study, in 80.5% of cases of major or CRNM bleedings, the site of bleeding was gastrointestinal or genitourinary. 5 In the CARAVAGGIO study, 32.6% of tumors were gastrointestinal and 11.5% genitourinary; although not exceeding bleedings in the dalteparin arm, 29.7% of major and/or CRNM bleedings with apixaban involved the gastrointestinal, and 31% the genitourinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Although we have made great progress in the diagnosis and treatment of digestive system tumors, most patients are already in the middle and late stages of cancer when they are diagnosed due to the difficulty of early diagnosis, and their treatment and prognosis are very poor. [ 18 ] Therefore, the molecular mechanism and early prediction of the occurrence and development of cancers are currently hot issues in research.…”
Section: Discussionmentioning
confidence: 99%